VALIDITY OF HANDS ON MINDS ON STUDENT WORKSHEET OF THE DANGERS OF PSYCHOTROPIC USE SUBMATERIAL - Indah Nur Fauziah; Raharjo Raharjo (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2018)
The dangers of psychotropic use and its effect towards health is a close phenomenon in students’ daily life. This submaterial asks the students to conduct anti-drug campaign in their school and local communities to fulfill the basic competence of Curriculum 2013. To meet this basic competence, students should have proper communication skill hence they can deliver the message effectively. Hands on minds on student worksheet allows the integration between daily life phenomenon and the topic that taught in the class. The aim of this development research was to describe the feasibility of student worksheet based on experts validation. This research used ADDIE method. The result of the validity was the developed hands on minds on worksheet got a score of 89% and categorized very valid. It can be concluded that the worksheet was feasible based on its validity. Key words: student worksheet; hands on minds on; psychotropic; communication skill.